Factors That Influence Successful Online Business Among Students in Universiti Malaysia Sabah - Mohd Syamezie bin Rusdi; Nursyahfika binti Muhammad Yaman; Shufirahziana binti Takin; Mohd Fauzi Helmi; Caroline Geetha (Penerbit UMS, 2021)
The study aims to identify the factors that influence the success of online business among undergraduates from Universiti Malaysia Sabah. This exploratory study involved 30 students from the Faculty of Business, Economics and Accountancy, Universiti Malaysia Sabah. The students were chosen using the convenient sampling method. The research tool used was a questionnaire. The result was analyzed using descriptive as well as inferential methods. The result revealed that the knowledge of financial management, time management as well as marketing skills and usage of the mobile app was the factors that influence the success of the online business among the students.